Identifikasi S.mutans dan S.sobrinus dengan Morfologi Koloni dan Analisa Biokimia - Heriandi Sutadi; Yuke Heriandi (Faculty of Dentistry, Universitas Indonesia, 2015)
Mutans streptococci are considered as major bacteria in human dental caries, and S. mutans and S. sobrinus are the ones most commonly found in humans. It has been shown from previous study that the numbers of S. sobrinus in oral samples are usually underestimated, and the S. sobrinus colonies are often misidentified as S. mutans. The aim of this study was to identify S. mutans and S. sobrinus from dental plaque of children. Dental plaque samples were collected using sterile cotton swabs from first and second upper deciduous molars from 3 children. Samples of dental plaque were inoculated onto MSB-0.5% yeast extract-20% sucrose. Identification of S.mutans and S. sobrinus was performed using examination of colony morphology and biochemical analysis with inulin and rafinose. Identification results were then documented as digital images with Olympus Digital BX 51. S. mutans forms convex, translucent colonies with rough margins, while the S. sobrinus colonies are translucent, circular, with pinpoints and smooth margins. Aglisining bubble often accumulates on top of the colony when excessive glucan is synthesized from sucrose. Biochemical analysis had showed positive reaction on S. mutans, and negative on S. sobrinus. From this study it can be concluded that S. mutans and S. sobrinus could be identified clearly with examination of colony morphology and biochemical analysis.